UNLOCKING MEANINGFUL HIGHER EDUCATION: A CONCEPTUAL EXPLORATION INTO THE TRIARCHIC CONNECTION OF KNOWLEDGE, TEACHING AND LEARNING - Anis Shaari; Berlian Nur Morat, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The term education generally constitutes knowledge delivery and attainment activities. Enabling an individual to both gain and exercise knowledge, the processes of teaching and learning have remained the backbone of the education milieu. A major challenge is how to translate the concepts of knowledge, teaching and learning into producing meaningful education. The effort requires a closer look into understanding the connection between such concepts in a constructive manner. Instead of viewing teaching and learning as merely a physical process of imparting, absorbing and regurgitating knowledge between educators and learners as what Paulo Freire terms as ‘banking education’, this paper aims at highlighting the three educational fundamentals and their connectedness to one another in the voice of emancipating education. It is anticipated to be significant to several educational stakeholders like educators, parents and learners, especially in recognising the real potential of an individual and education, when knowledge, teaching and learning should no longer be viewed as transmissionary in nature.